"Jinja" Perusahaan sebagai Pusat "Shaen" - Lawanda, Ike Iswary (Wacana, Journal of the Humanities of Indonesia, 2003)
This paper demonstrates that jinja as the center of shaen functions to remind every worker of the existence of shaen in order to make her feel the power and authority of the sacred being near them, in time and space surrounding them to protect business and maintain security in work. Jinja, owned and founded by the corporation, becomes the symbolic representation of the sacred; worshipped by employees it becomes the site (ba) to conduct corporate ritual (matsuri). The existence of jinja in the Japanese corporation and in the space of production implies the belief of workers that the sacred is existent and immanent in the corporation. The belief that the sacred and the profane exist produces an order and social control amongst and over the workers and encourages productivity. That is, they constitute a symbolic expression of their belief based on, and the same time constructing, the Japanese work ethic.